AKAD MURABAHAH DALAM INVESTASI LOGAM MULIA PADA PEGADAIAN SYARIAH BANJARMASIN - RAHMI, NISPAN (Islamic Economics and Business Faculty of UIN Antasari, 2015)
Abstract: In the research on the Majesty product in the Islamic pawnshop, it can be known t h a t o n e o f i t s c o n t r a c t u s e mu r a b a h a h c o n t r a c t . B a s e d o n i t s m e ch a n i s m f o r N o b l e metal investment can be done through several procedures: (1) T he booking procedure which includes the vital preconditions that must be met by the customers to invest noble.(2) Giving procedures consist of the steps of giving noble metal investment to customers which are divided into two processes, such as product precious cash cycle and credit Majesty product cycle. (3) The settlement procedure is a noble form of the payment system that also divided into two systems, namely by way of repayment at once (cash) or by way of installments in accordance with an agreement made in advance by both parties.